Retrospective Evaluation of Forensic Medicolegal Childhood Deaths Among Children Aged 0-6 Years - Yıldırım, Ali; Polater, Erdoğan; Bütün, Celal (The Bulletin of Legal Medicine, 2020)
Objective:The aim of this study was to analyze the epidemiological pattern and characteristics of forensic cases resulting in death among children aged 0-6 years and to discuss the solution offers in order to prevent such events that may result in death in 0-6 years of childhood.Materials and Methods:73 cases of medicolegal childhood death among children aged 0-6 years whose post-mortem examinations, dead body examinations and/or autopsies were performed at the morgue of the Cumhuriyet University Hospital in a 8-year period between January 1, 2008 and December 31, 2016 were included in the study group and retrospectively analyzed. In all statistics, the SPSS v.20 statistical software was used, and a p value of
Keywords: Forensic Medecine; Pediatric deaths; Epidemiological Pattern; Cause of Death